Influence of gestational weight gain and maternal depression on offspring BMI trajectory from birth to 3 years: A longitudinal mother-infant study - Ting Zeng; Ting Huang; Liangqiong Deng; Li Xiong; Peipei Zeng; Ji Peng; Qiulan Wang; Ling Chen; Yu Zhang; Dingyuan Zeng (PLoS ONE, 2025)
Objective Gestational weight gain (GWG) is associated with offspring growth trajectories and early childhood obesity, but existing studies rarely account for maternal psychological status, which may confound or modify this association. This study aimed to evaluate the impact of GWG patterns on offspring body mass index-for-age Z score (BMI-Z) trajectories from birth to 3 years, adjusting for maternal depression and examining effect modification by depressive symptoms. Methods This mother-infant paired longitudinal cohort study was conducted between September 2019 and September 2024 at the Liuzhou Maternity and Child Healthcare Hospital. Data on maternal sociodemographic characteristics, health status, lifestyle factors, clinical and anthropometric measurements were collected. Linear mixed-effects models were used to assess the association between GWG patterns and offspring BMI trajectories, adjusting for maternal pre-pregnancy BMI, sociodemographic factors, and maternal depression status. Stratified analyses by depression status were conducted to explore effect modification. Results A total of 1,133 mother-infant pairs were included in this study. Offspring of mothers with excessive GWG showed higher BMI-Z scores after 24 months. Children born to underweight mothers had lower BMI-Z scores throughout follow-up. Mixed-effects modeling indicated that both pre-pregnancy BMI and GWG pattern were independently associated with BMI-Z trajectories (P < 0.05). After adjusting for depression scores, the association between overweight/obesity (β = 0.48, 95% CI: 0.23–0.76, P < 0.001) as well as excessive GWG (β = 0.17, 95% CI: 0.04–0.29, P < 0.05) and child BMI trajectory persisted. Maternal underweight was still negatively associated with child BMI z -scores (β = −0.35, 95% CI: −0.52 – −0.15, P < 0.001). Stratified analyses showed that the effect was more pronounced in mothers with depressive symptoms (P < 0.05). Conclusion Excessive GWG significantly influences early childhood growth patterns. Maternal depressive symptoms may partially confound or modify this association. These findings highlight the need to integrate psychological assessments into prenatal care to optimize offspring growth trajectories and reduce the risk of early-life overweight.